Ethnic Chinese business in Asia : history, culture and business enterprise - Yen, Qinghuang ([Hackensack], New Jersey : World Scientific, 2013)
"Provides a broad introduction to the ethnic Chinese business in Asia, with focus on the ethnic Chinese in East and Southeast Asia. The growing interest in ethnic Chinese business reflects its importance in these two regional economies, and its relations with China's economy--the world's new economic powerhouse. It examines the nature and characteristics of the ethnic Chinese business, such as business networks, family business and conglomerates, concepts of xinyong and guanxi, and entrepreneurship and management. It also examines the input of history and culture in the formation and operation of ethnic Chinese business. The second half of the book is devoted to detailed regional studies, covering the Chinese in Thailand, Malaysia and Singapore, Indonesia, the Philippines, Hong Kong and Taiwan"--
Keywords: Corporations, Chinese -- Asia; Chinese -- Asia -- Economic conditions; Business networks -- China; Business networks -- Asia; International business enterprises -- China; International business enterprises -- Asia; Entrepreneurship -- China; Entrepreneurship -- Asia